The Geocriticism of Mehdi Akhavan-Sales and Abd al-Wahhab Al-Bayati Poetry; The Analysis of the Homeland’s Image in Akhavan-Sales and Al-Bayati Poetry - Baharak Valineya (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
In this study, in order to investigate how the poetry is connected to a place or, in a more unequivocal way, to the space, the patriotic poems of Mehdi Akhavan-Sales and Abd al-Wahhab Al-Bayati were studied and the analysis of the homeland’s image in their poetry was conducted employing an interdisciplinary approach utilizing the theoretical foundations and the research method of geocriticism. the analysis shows that: 1. in the poems of Akhavan-Sales and Al-Bayati, the home land is a space that essentially holds a cultural and anthropomorphic representation, not merely a passive scene and a piece of land or a fragment of natural geography with mountains and water and sea and plain; the home land = place + human. 2. Their view toward the homeland is sometimes romantic: when the poet is so passionate about the homeland—and whatever belongs to it—that he cannot tell them apart, or when he recognizes his helpless and forlorn homeland as “the leafless garden” or “grave land” or “stone land city” with a deep sadness. What we find as the homeland in Akhavan-Sales and Al-Bayati Poetry is an image, the homeland’s image. 4. The form and the variation of this image is not identical in their poem; the homeland image in Al-Bayati’s poem is a broad and flowing presentation, while in Akhavan-Sales’ poem it is not that broad and when he talks about the homeland, he only refers to Iran.